Perbandingan Kinerja Perbankan Syariah Antara Sebelum dan Saat Terjadi Pandemi Covid-19 - Paramita Amitarwati, Diah; Prabowo, Agung; Supriyanto, Supriyanto; Supriyono, Supriyono; Suwali, Suwali (Perwira Journal of Economics & Business, 2023)
The Covid-19 pandemic has had a tremendous impact on all walks of life. The economic sector is one experienced a worsening impact and the banking sector is no exception. Sharia banking will complex challenges when compared to conventional banking considering caused Sharia banking used a profit-sharing contract. For this reason, it is necessary to conduct research that analyzes the performance of Sharia banking during the Covid-19 period. The performance in this study focuses on aspects financing of distribution. The purpose of this study was determined the difference performance of Sharia banking between before and during covid-19, with three variables of TPF, FDR and NPF. The second objective is to see the effect of the three independent variables partially and simultaneously on banking performance both before and during Covid-19. This type of research is quantitative. Statistical tests used include t test, F test, and linear regression. The data used is secondary data obtained from the Indonesian Banking Statistics Report issued by the Financial Services Authority. Data processing is used SPSS. Data period before the pandemic took of January-December 2019 and during the pandemic took of January-December 2020. The results of this research, FDR variable has differences between before and during the Covid-19 pandemic. There is no difference between TPF and NPF variables before and during the Covid-19 pandemic. The results of the second study stated that the TPF and FDR variables had partial and simultaneous effect on the performance of financing distribution, while the NPF variable had no effect either partially or simultaneously on the financing performance of Sharia Banking.